An application of Bloom's taxanomy in generation and assessment of examination question items - Nordin, Azlin; Harasid, Haizir; Anuar, Mohamad Ruzaini; Kamis, Norazlina (UTM, 2014)
The objective of this development research is to explore the application of Bloom’s Taxanomy in the generation of examination question items process. In addition, assessment of the item’s complexity will also be addressed. This paper provides the explanation, description and information about the Generation and Assessment of Examination Question (GAEQ) for the use of the lecturers in higher learning institute. The current process to generate the examination questions and assess their complexity is done separately and manually. The contribution of this paper is the integration of Bloom’s Cognitive Domain in both generating and assessing the examination question. The assessment process will automatically measures the complexity level of the question items. GAEQ will then compile those items and create a complete final examination question set. Hence, it is the aim of the GAEQ system to initiate and develop a system to assist the lecturers in producing quality examination question.